FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN UANG NON TUNAI (Studi Kasus : Indonesia, 2009:1 – 2014:9) - Azmi Azhari (Jurnal Ilmiah Mahasiswa FEB, 2014)
This study analyzed the effect of per capita GDP, interest rates, and inflation on nominal credit card transactions and nominal debit card and ATM transactions in Indonesia.Upaya increased use of non-cash payment instruments such as credit cards and debit cards and ATM could not be separated from the influence of a variety of indicators including macroeconomic variables, due to non-cash payment instruments is one type of demand deposits held by the public. By using analytical tools error correction models it was concluded that the more that people tend to use debit and ATM card from a credit card because of the influence of macroeconomic variables that may pose a greater risk in using a credit card. Keywords: Macroeconomics, credit card, debit and ATM cards, error correction models.